Memberikan Informasi Tentang Kebudayaan Tiongkok Dalam Program Siaran "Wo Ai Metta" di Radio Metta Fm - Dian Prasetyo Adi (Jurnal Pengabdian dan Pengembangan Masyarakat, 2021)
"Wo Ai Metta" or I Love Metta is a broadcasting program that provides information about the Chinese culture and presents the Mandarin songs. In this study, the author discusses the findings discovered while on the university's Tri Darma program, particularly while performing the community service regarding the contents presented in "Wo Ai Metta" in Metta FM, Surakarta. Where the contents including: basic skills in Chinese (listening, speaking, reading and writing), Chinese grammar, Chinese culture, translation skill, and other latest issues, which make the program even more interesting and advantageous. The purpose of this study is to acquire the data of how "Wo Ai Metta" broadcasting program plays a role in giving the information pertaining to the Chinese culture. It is a qualitative study where the data were obtained through observation, deep interview and documentation, and analyzed using the case study approach. The findings show that  "Wo Ai Metta" must be presented in a way that informative, interesting, and easy to understand. "Wo Ai Metta" has a role to provide information and entertainment about the Chinese culture. As most of the listeners are people of Chinese descent, so very often the messages are sent in Chinese.